Changes in soil biochemical properties associated with Ligularia virgaurea spreading in grazed alpine meadows - Xiao Ming Shi; Xiao Gang Li; Rong Mei Wu; Yun Hui Yang; Rui Jun Long (Plant and Soil, 2011)

Homology modeling, molecular docking and spectra assay studies of sterol 14α-demethylase from Penicillium digitatum - Shuxiang Li; Jianhua Zhang; Shufen Cao; Rui Han; Yongze Yuan; Jiangke Yang; Yunjun Yan; Deli Liu (Biotechnology Letters, 2011)

Retinoids induced Pck1 expression and attenuated insulin-mediated suppression of its expression via activation of retinoic acid receptor in primary rat hepatocytes - Yan Zhang; Rui Li; Wei Chen; Yang Li; Guoxun Chen (Molecular and Cellular Biochemistry, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

Erratum to: Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)